Descrição de morfotipos de vespas parasitoides da subfamília Cryptinae (Hymenoptera: Ichneumonidae) encontrados em uma mata mesófila semidecídua no município de Ituiutaba-MG - Barrada, Lorraine Mendes (2019)
Ichneumonidae is a group considered extremely important in the parasitic series. Despite the importance, in Brazil the group is less studied and possibly many species and genera have not yet been described. The main objective of this research is to describe the morphotypes of the Subfamily Cryptinae (Hymenoptera: Ichneumonidae) collected in semideciduous forest in the municipality of Ituiutaba- MG. The specimens were collected using Moericke or Pantraps traps. To describe the morphotypes we used simple morphometry, such as body, wing and ovipositor length. Fifty-seven specimens of the Cryptinae subfamily were collected, divided into seven morphotypes by comparing their measurements body and colors. The morphotype with the highest abundance was 2, with 24 specimens. It was possible to observe a large variation in the means of size of the specimens, morphotype 1 was the one with the highest means, with 12,5 ± 0,7 body length and 7,8 ± 1,1 mm ovipositor length while morphotypes 2 and 5 were the smallest, with an average body size length of 7 mm and the ovipositor with 2.5 mm. These results show the diversity of parasitoid species on site, and we suggest that further research is carried out to better understand the fauna of the group in the region.